A COLREG-compliant ship collision alert system for stand-on vessels. (15th December 2020) - Du, Lei; Valdez Banda, Osiris A.; Goerlandt, Floris; Huang, Yamin; Kujala, Pentti
Abstract: Bridge alarms are a plausible way to reduce the ship collision probability by timely alerting the officer on watch of a conflict. However, there currently are no dedicated methods for alerting a stand-on ship to compensate the unawareness of or inactive response of a give-way ship to dangerous encounter situations. Therefore, this article proposes a collision alert system from the stand-on ship perspective to trigger the stand-on ship's involvement in the conflict elimination. The developed method quantifies the terms of the COLREGs regarding the stand-on ship's responsibility for conflict elimination. The conflict severity is divided into 9 classes based on the ship intention estimation, conflict evolution analysis and COLREGs scrutiny. These are linked with the 4 stages of the encounter process to helps stand-on ship clarify her action responsibilities as per the rules and classify the alert into four levels. The available maneuvering margin of the stand-on ship is considered to improve the accuracy of severity ranking. The results of several case studies in open water with good visibility indicate that the proposed method can support the stand-on ship to correctly understand the rules and to fulfil her duties. Highlights: A COLREG-compliant ship collision alert system for the stand-on ship is proposed. The terms of the COLREGs regarding the stand-on ship's responsibility for conflict elimination are quantified. Available maneuvering margins of the stand-on ship is considered to improve the severity ranking accuracy. Conflict severity is divided into 9 classes based on the ship intention estimation and conflict evolution analysis.